Acoustic and morphological differences in Colinus genus (Galliformes: Odontophoridae) support the occurrence of four species - Sandoval, Luis; Barrantes, Gilbert; Fuchs, Eric J.; Ocampo, Diego (Revista de Biología Tropical, 2025)
Introduction: The taxonomy of Galliformes species, a group closely associated with humans since antiquity, remains unclear at various taxonomic levels, producing taxonomic changes constantly. Objective: Our objective is to provide morphological and acoustic data to support the recent taxonomic recognition of Colinus leucopogon (Spot-bellied Bobwhite) as a distinct species from Colinus cristatus (Crested Bobwhite). Methods: Using a combination of morphological and acoustic analyses, we assessed the differences between these two recently recognized species and compared them with the two other well-established species within the genus: C. nigrogularis (Black-throated Bobwhite) and C. virginianus (Northern Bobwhite). Results: Our acoustic analysis of male songs from 64 individuals showed significant differences in maximum amplitude frequency, song duration, and number of elements, which can act as a reproductive barrier between C. cristatus and C. leucopogon. Morphological analyses, however, revealed only limited differences, primarily in tarsus length and wing chord length. Conclusions: Our findings suggest that while male song characteristics strongly support the recognition of C. cristatus and C. leucopogon as distinct species, morphological differences are less pronounced, potentially due to ecological factors such as habitat similarity and altitudinal distribution. This study highlights the importance of including both acoustic and morphological traits in resolving taxonomic uncertainties and understanding species boundaries in Galliformes.